A systematic literature review of intersemiotic translation and meaning - Yubin, Zheng; Husain, Salina; Mohd Jalis, Farhana Muslim (Academy Publication, 2025)
—The essence of translation activities lies in the transformation of meaning. How to better convey meaning has always been a central topic in translation studies. However, this exploration has traditionally focused on the meaning of linguistic signs. With the introduction and increasing application of intersemiotic translation, the expression of meaning at the non-verbal signs level has also gained importance. This systematic literature review aims to discuss studies related to intersemiotic translation and meaning to gain a more holistic understanding of the research perspectives, theoretical approaches, and research findings. Using the PRISMA framework, this study analyzed 27 included publications from the Scopus and CNKI databases. The findings reveal that what takes up more are the researches on meaning of intersemiotic translation of literary texts from verbal signs to non-verbal signs. The generation of meaning explained through semiotics and theories from other disciplines is feasible, while many studies lack sufficient theoretical grounding. Intersemiotic translation can positively facilitate the generation and transformation of meaning but also carries a certain risk of distorting the original intent.